The Montréal School: Urban Social Mix in a Reflexive City - Germain, Annick (Anthropologica, 2013)
Could Montréal be a new "school" in urban studies in North America? This paper shows how research on social and ethnic mix in Montréal has been built on what makes this city unique: its "in-between" nature, its neighbourhoods and the importance of public spaces in urban life. The research agenda is also part of a conversation between scholars and practitioners that has continued uninterrupted for almost 30 years. This is illustrated by revisiting a series of research projects conducted on three topics: inter-ethnic cohabitation in neighbourhoods, in social housing, and planned social mix.